Flow and Convective Heat Transfer of Cylinder Misaligned from Aerodynamic Axis of Cyclone Flow - I. L. Leukhin; E. N. Sаbourov; I. A. Usachov; V. Gаrеn (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper provides and analyzes results of experimental investigations on physical specific features of hydrodynamics and convective heat transfer of a cyclone flow with a group of round cylinders located symmetrically relative to its aerodynamic axis, calculative equations for average and local heat transfer factors at characteristic sections of cylinder surface.